Towards european references for teacher education: challenges to teacher educators - Bártolo Paiva Campos (2006)
The first purpose of this presentation is to identify some possible common European references for teacher education policies in the work undertaken up until now by the Expert Group "Improving the Education of Teachers and Trainers", set up by the European Commission as part of the follow-up of Common Objectives of European education and training systems Process.